Perancangan Sistem Pendukung Keputusan Penyeleksian Beasiswa Menggunakan Metode SAW - Ami Anggraini S; Edidas Edidas; Denny Kurniadi (Universitas Negeri Padang, 2014)
Scholarship is income for those who receive it and the purpose of thescholarship is to help ease the burden of the cost of education students receiver.Through the Directorate General of Higher Education scholarship disbursement isdone by several agencies to help someone less capable in economic terms and forthose who have achievements . and the State University of Padang is one of thecolleges that distribute scholarships to students each semester .At the Faculty of Engineering, State University of Padang distributedscholarships PPA and BBM annually. The selection of who is entitled to get thescholarship using the calculation of the specific criteria. These criteria, namely, thecumulative achievement index, total parental income, number of dependent parental,and semester. For the sake of the effectiveness, taking the right decision is needed.For it is necessary to develop a decision support system that can help the process,and in the development of this system is used SAW method.SAW method is a method for determining who is entitled to receivescholarships based on predetermined criteria . The process begins by finding theweights for each criterion , and then rank the ranking based on the amount of thehighest weight value obtained from each alternative . Alternative that has the highestamount of weight that is more entitled to get a scholarshipKeyword : Scholarship, Decision Support Systems, SAW, JSP.